2011
DOI: 10.1159/000322582
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Cell Protein C Receptor: Endothelial Regulation and Cumulative Impact of Gender and A3 Haplotype

Abstract: Background: The endothelial cell (EC) protein C receptor (EPCR) negatively regulates coagulation and inflammation. Factors and mechanisms regulating the expression of cell-bound EPCR and the release of soluble (s) EPCR are still unclear. Methods: We investigated the reciprocal regulation of membrane-bound and sEPCR upon inflammation using primary cultures of vascular EC. The impact of 2 parameters, gender and EPCR gene A3 haplotype, on sEPCR plasma basal level and endothelial expression was examined by Elisa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 78 publications
4
6
0
Order By: Relevance
“…In previous studies, sEPCR levels in septic patients were found to be significantly higher [12,26], similar [27], or even lower [28] than in healthy volunteers. These results confirm our previous data indicating that gender was a critical parameter determining basal levels of sEPCR [29]. Moreover, we observed here that gender ratio may be another key factor affecting D1 sEPCR in septic patients.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, sEPCR levels in septic patients were found to be significantly higher [12,26], similar [27], or even lower [28] than in healthy volunteers. These results confirm our previous data indicating that gender was a critical parameter determining basal levels of sEPCR [29]. Moreover, we observed here that gender ratio may be another key factor affecting D1 sEPCR in septic patients.…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed recent data [31] demonstrating that gender strongly correlates with sEPCR levels, with higher circulating sEPCR levels observed in males. We found a strong association between diabetes and sEPCR levels.…”
Section: Discussionsupporting
confidence: 92%
“…Further studies are needed to investigate the relationship between EPCR membrane expression and its circulating form. Indeed, a recent study reported that TNFα causes a rapid down-regulation of membrane associated EPCR expression without markedly affecting the spontaneous release of sEPCR by arterial endothelial cells [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Four haplotypes are defined by the SNPs: H1–H4 [ 18 20 ]. The H3 haplotype has been associated with increased plasma sEPCR levels [ 19 , 22 , 23 ] and has been suggested to be a risk factor for venous thrombosis [ 19 , 21 ], although other studies could not confirm this [ 18 , 20 ]. Contrary to H3, the H1 haplotype has been associated with elevated APC plasma concentration and a protective effect against venous thrombosis [ 20 , 24 ].…”
Section: Introductionmentioning
confidence: 99%